a Industrial Revolution 4.0 as a Strategic Issue of Higher Education (International Journal of Scientific Research and Management (IJSRM), 2022)
This study aims to explore strategic issues of the industrial revolution 4.0 in the higher education environment, accompanied by an in-depth analysis with the perspective of change management and how they adapt. The method used is SWOT analysis by scanning the environment through non-probability sampling using snowball data collection with the help of Google forms so that stakeholders can respond through a multimedia platform. The results of data processing in the form of index numbers by contrasting strengths and weaknesses as well as opportunities and threats. The final result is the ordinate point 2.93, 013 which is in quadrant 1 with good internal strength but has not been able to seize opportunities, which requires more adequate consolidation of resources. It was concluded that private higher education in Banten Province at a young age still requires strengthening in terms of human resources, finances, stable intake of students and educational infrastructure that must be updated according to the demands of the industrial revolution 4.0.